Scribing Method for Carbon Perovskite Solar Modules - Simone Meroni (Energies, 2020)
The fully printable carbon triple-mesoscopic perovskite solar cell (C-PSC) has already demonstrated good efficiency and long-term stability, opening the possibility of lab-to-fab transition. Modules based on C-PSC architecture have been reported and, at present, are achieved through the accurate registration of each of the patterned layers using screen-printing. Modules based on this approach were reported with geometric fill factor (g-FF) as high as 70%. Another approach to create the interconnects, the so-called scribing method, was reported to achieve more than 90% g-FF for architectures based on evaporated metal contacts, i.e., without a carbon counter electrode. Here, for the first time, we adopt the scribing method to selectively remove materials within a C-PSC. This approach allowed a deep and selective scribe to open an aperture from the transparent electrode through all the layers, including the blocking layer, enabling a direct contact between the electrodes in the interconnects. In this work, a systematic study of the interconnection area between cells is discussed, showing the key role of the FTO/carbon contact. Furthermore, a module on 10 × 10 cm2 substrate with the optimised design showing efficiency over 10% is also demonstrated.